Effects of Massage Therapy on Physical Performance and Perceived Recovery following Acute Eccentric Exercise in Male Body Building Athletes - Mohsen Teimouri; Mehdi Kargarfard; Gholam Reza Sharifi (مجله دانشکده پزشکی اصفهان, 2012)
Background: Massage therapy is one of the methods used to improve and prevent sports injuries. The purpose of this study was to examine the effects of an athletic massage after acute eccentric exercise on physical performance and perceived recovery in male body building athletes. Methods: Thirty male body building athletes were selected and randomly divided into two groups of experimental (n = 15) and control (n = 15). They performed 5 sets of ten maximal eccentric contractions at a level of 80 ± 5% of a one-repetition maximal contraction of the knee flexors and extensors at maximal angular velocity. The experimental group received athletic massage using massage techniques for 30 minutes immediately after exercise, whereas the control group was instructed to maintain their current lifestyle. Physical performance and perceived recovery were assessed using the Sargent jump test and perceived recovery questionnaire before and immediately after exercise, and at 2, 24, 48 and 72 hours after exercise. The obtained data was analyzed using repeated measures analysis of variance (ANOVA).. Findings: : Significant reductions in physical performance as well as significant increments in muscle soreness were observed in both groups after acute exercise. However, the results showed significant improvements in physical performance and perceived recovery in the experimental group compared with the control group 24 hours after massage therapy (P < 0.05). Conclusion: These results suggest that a massage therapy session may improve the physical performance and perceived recovery following acute eccentric exercise in male body building athletes. However, it may not be beneficial in the treatment of strength and functional declines.